A study on risk assessment techniques in information systems - Nagamalleswari, D; Nagalakshmi, J; Karthik, G; Harthita, P (International Journal of Engineering and Technology, 2017)
In today’s world, IT industry is rushing forward with an advancement of developing the advanced software. The Developers always try to develop the software projects without any errors or failures. Even though the developers take many measures to avoid software project failures, they are facing the failures that are occurred due to Risks that take place in the software projects. We cannot remove risk completely to the 100% extent, but we can try to minimize the risk in the projects by assessing the risks. So, in this paper we are providing a survey which overviews on different risk assessment techniques. This survey provides information about various risk assessment techniques which will be further useful for the software developers to minimize the risk and make the successful project.